2019
DOI: 10.1128/aac.00208-19
|View full text |Cite
|
Sign up to set email alerts
|

Link between Heat Shock Protein 90 and the Mitochondrial Respiratory Chain in the Caspofungin Stress Response of Aspergillus fumigatus

Abstract: Aspergillus fumigatus is an opportunistic mold responsible for invasive aspergillosis. Triazoles (e.g., voriconazole) represent the first-line treatment, but emerging resistance is of concern. The echinocandin drug caspofungin is used as second-line treatment but has limited efficacy. The heat shock protein 90 (Hsp90) orchestrates the caspofungin stress response and is the trigger of an adaptive phenomenon called the paradoxical effect (growth recovery at increasing caspofungin concentrations). The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Subsequently, we investigated the metabolic activity of the mature A. fumigatus biofilm consisting of hyphal cells exposed to HS. The 2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide salt (XTT) assay was employed to test the biofilm response to HS as previously described (Dhingra, Buckey, & Cramer, 2018). Consistent with the observed decrease in conidia viability, biofilms of pkcA G579R and ΔmpkA strains also exhibited a significant decrease in metabolic activity when the biofilm was incubated for 60 or 120 min at 48 C (Figure 1b).…”
Section: Cwip Mutants Are Less Tolerant To Hssupporting
confidence: 58%
See 1 more Smart Citation
“…Subsequently, we investigated the metabolic activity of the mature A. fumigatus biofilm consisting of hyphal cells exposed to HS. The 2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide salt (XTT) assay was employed to test the biofilm response to HS as previously described (Dhingra, Buckey, & Cramer, 2018). Consistent with the observed decrease in conidia viability, biofilms of pkcA G579R and ΔmpkA strains also exhibited a significant decrease in metabolic activity when the biofilm was incubated for 60 or 120 min at 48 C (Figure 1b).…”
Section: Cwip Mutants Are Less Tolerant To Hssupporting
confidence: 58%
“…Cooperating mechanisms between the CWIP and Hsp90 function have been observed in A. fumigatus since mutants of these genes are concomitantly more susceptible to CW stress and elevated temperatures (Lamoth, Juvvadi, Fortwendel, & Steinbach, 2012; Rocha et al, 2015; Valiante et al, 2009). Also, hsp90 mediates the caspofungin paradoxical effect (Aruanno, Bachmann, Sanglard, & Lamoth, 2019; Lamoth, Juvvadi, Gehrke, et al, 2014; Lamoth, Juvvadi, Soderblom, et al, 2014). At the protein level, the MpkA homologues in yeast and C. albicans are known Hsp90 clients (Diezmann, Michaut, Shapiro, Bader, & Cowen, 2012; LaFayette et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of respiratory inhibitors results in significant decreases of the caspofungin MICs for C. parapsilosis (39). Caspofungin exposure induces expression of A. fumigatus mitochondrial respiratory chain genes, specifically NADH-ubiquinone oxidoreductases (complex I), while CPE is abolished by addition of rotenone, a complex I inhibitor (58). Interestingly, those authors also described a connection between rotenone inhibition and increases in intracellular calcium concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…However, there may be other downstream effectors in the complex network of Hsp90. Very recently, the mitochondrial respiratory chain was shown to play a role in the PE, and activation of mitochondria in response to caspofungin was dependent on Hsp90 (27).…”
mentioning
confidence: 99%
“…Analyses of the intracellular trafficking of the different actors of the Hsp90calcineurin pathway showed that calcineurin and calmodulin localized at the hyphal tips and septa and that Hsp90 moves from the cytosol to the cell wall and sites of septa formation in the presence of caspofungin (27)(28)(29)(30). Physical interaction between Hsp90 and calcineurin has been demonstrated in yeasts (31).…”
mentioning
confidence: 99%